Digital Transformation in Improving the Quality of Member Services at KPRI Makassar State University - Tuti Supatminingsih; Andi Asti Handayani (Darul Yasin Al Sys, 2026)
Digital transformation has become both a challenge and a strategic necessity for cooperatives in improving the quality of member services in the era of information technology. KPRI Makassar State University, as an employee cooperative within a university environment, faces service challenges related to the limitations of conventional administration, suboptimal access to information, and increasing member demands for fast, transparent, and digital-based services. This study aims to analyze the implementation of digital transformation in improving the quality of member services at KPRI Makassar State University and to identify its impacts and implementation obstacles. A qualitative case study design was employed. Data were collected through in-depth interviews, observations, and documentation involving cooperative administrators, administrative staff, and cooperative members selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings show that digital transformation improves the quality of member services through administrative digitalization, online service systems, digital payments, and faster, more transparent technology-based communication. Digital transformation positively contributes to the service quality dimensions of reliability, responsiveness, assurance, empathy, and tangibles. However, the study also identifies obstacles related to members’ limited digital literacy and insufficient human resources in information technology. This study concludes that digital transformation is an important strategy for modernizing cooperative services. The findings contribute to the literature on cooperative service innovation and provide practical implications for strengthening digital competencies, developing technology-based service systems, and implementing sustainable cooperative digitalization policies to increase member satisfaction and loyalty.